Figures of Speech of Love in Suntaraporn Songs - Phakkhaphanon, Sunan (University of the Thai Chamber of Commerce Journal Humanities and Social Sciences, 2018)
Suntaraporn love-songs are remarkably written with elaborate use of figures of speech. Fifty of Suntaraporn love-songs from the album “The Greatest of Suntaraporn Love Songs” were analyzed in order to see how the figures of speech – simile and hyperbole – were used to convey or depict the song meanings, pictures, and emotions. The findings reveal that the figures of speech were used to 1) bless the beauty of the beloved woman, 2) promise to the beloved one to be confident in love, and 3) depict separation from love leading to suffering, sadness, and depression. Moreover, the use of figures of speech in Suntaraporn love-song relics is selected in accordance with the literary conventions in three styles, as follows, a) to bless the beauty of a woman, the song writers often compare her beauty to nature, individuals, or gods, b) to convey the meaning of promise, simile was used to relate the words of promise to nature and the concepts of Buddhism, and c) to depict the feelings of suffering, sadness, and depression, caused by being separated from the beloved, simile was used to compare separation to the lost in one’s life and nature.